An epidemiological study of tobacco-related oral habits in Mahabubnagar district of Telangana, India - Ramesh K Koothati; Gangili Vivekanandh Reddy; Gantala Ramlal; Leela K Prasad; Venkateshwarlu James Anil Kumar; Archana Pokala (Wolters Kluwer Medknow Publications, 2017)
Aim: To assess the prevalence of tobacco-related oral habits (TROH) in Mahabubnagar district of Telangana, India. Materials and Methods: A cross-sectional study was conducted among 3200 participants in Mahabubnagar district of Telangana, India. People aged 16-75 years and both men and women in same proportions were included in the study. Data was obtained by interviewing individual participants regarding various TROH. Results: Out of 3200 participants, 750 (23.44%) had TROH, whereas 2450 (76.56%) did not have any tobacco habits. In 750 participants who had TROH, the habit of tobacco chewing was more common (44.5%) followed by the habit of smoking (42.7%) and both smoking and chewing (12.8%). Conclusion: From the present study, we can conclude that prevalence of TROH is alarmingly high in this district. Oral physicians have an important role in tobacco control as they can directly see the harmful effects of tobacco in the mouth.